2013
DOI: 10.1590/s0034-737x2013000300010
|View full text |Cite
|
Sign up to set email alerts
|

Teor e composição química do óleo essencial e crescimento vegetativo de Aloysia triphylla em diferentes espaçamentos e épocas de colheita

Abstract: Content and constituents of essential oil of Aloysia triphylla in different row spaces and harvest timesThis study aimed to evaluate biomass production, content and components of the essential oil of Aloysia triphylla in different row spaces and harvest times. The experiment was conducted at the experimental area of Universidade Federal Tecnológica do Paraná -Campus Dois Vizinhos, from March 2010 to January 2012. The experimental design was a randomized block design with three replications in a factorial schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
(10 reference statements)
3
9
1
3
Order By: Relevance
“…Rodrigues et al (2012), evaluating the chemical composition of the essential oil of the leaves of the species also found α-pinene and β-caryophyllene among the major compounds. In contrast to this work, Paulus et al (2013) observed significant differences in the chemical composition of A. triphylla essential oil, grown at different spacings.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Rodrigues et al (2012), evaluating the chemical composition of the essential oil of the leaves of the species also found α-pinene and β-caryophyllene among the major compounds. In contrast to this work, Paulus et al (2013) observed significant differences in the chemical composition of A. triphylla essential oil, grown at different spacings.…”
Section: Resultscontrasting
confidence: 99%
“…The height (115.78±12.11 cm) and the diameter (26.79±5.00 mm) were not influenced. Paulus et al (2013) observed significant differences in height of the plants of the Aloysia triphylla specie, when cultivated at larger spacings (1.0 × 1.0 m). According to the authors, with a lower density, there was a uniform distribution of plants per area, facilitating the efficient use of light, water, and soil nutrients.…”
Section: Resultsmentioning
confidence: 85%
“…These results corroborate with the findings of Paulus et al (2013), which affirmed that the plant Aloysia triphylla, in southern Brazil, begin the loss of its leaves in the months of May and June, arriving at a 40% reduction of total leaf mass. During the months of June and July, at the end of autumn and early winter season, with the occurrence of frost, leaf loss rates can reach 100%.…”
Section: Meteorological Characterization and Analysis Of Variancesupporting
confidence: 90%
“…Plants that are adapted to warm seasons tend to restrict their growth outside of these ideal environmental conditions. Studies have been conducted with the Aloysia triphylla species (Brant et al, 2010;Paulus et al, 2013;Zeppenfeld et al, 2014;Ebadi et al, 2015;Dianat et al, 2016), since the species has aroused economic interest in the exploration of compounds with therapeutic properties.…”
Section: Introductionmentioning
confidence: 99%
“…A Aloysia triphylla (L'Hérit) Britton (Verbenaceae), popularmente, conhecida como cidrão e erva Luiza, é uma planta que apresenta folhas de grande importância medicinal, devia a presença de compostos químicos, empregados no combate a resfriados febris, além de ser antiespasmódica, eupéptica, estimulante, calmante e tônica (Paulus et al, 2013), sendo também usada para tratamento contra afecções do coração, histeria e melancolia (Lorenzi & Matos, 2008).…”
Section: Introductionunclassified